Plasticity in elk migration timing is a response to changing environmental conditions. (1st May 2019) - Rickbeil, Gregory J. M.; Merkle, Jerod A.; Anderson, Greg; Atwood, M. Paul; Beckmann, Jon P.; Cole, Eric K.; Courtemanch, Alyson B.; Dewey, Sarah; Gustine, David D.; Kauffman, Matthew J.; McWhirter, Douglas E.; Mong, Tony; et al.
Abstract: Migration is an effective behavioral strategy for prolonging access to seasonal resources and may be a resilient strategy for ungulates experiencing changing climatic conditions. In the Greater Yellowstone Ecosystem (GYE), elk are the primary ungulate, with approximately 20, 000 individuals migrating to exploit seasonal gradients in forage while also avoiding energetically costly snow conditions. How climate‐induced changes in plant phenology and snow accumulation are influencing elk migration timing is unknown. We present the most complete record of elk migration across the GYE, spanning 9 herds and 414 individuals from 2001 to 2017, to evaluate the drivers of migration timing and test for temporal shifts. The timing of elk departure from winter range involved a trade‐off between current and anticipated forage conditions, while snow melt governed summer range arrival date. Timing of elk departure from summer range and arrival on winter range were both influenced by snow accumulation and exposure to hunting. At the GYE scale, spring and fall migration timing changed through time, most notably with winter range arrival dates becoming almost 50 days later since 2001. Predicted herd‐level changes in migration timing largely agreed with observed GYE‐wide changes—except for predicted winter range arrival dates which did not reflect the magnitude of change detected in the elk telemetry data. Snow melt, snow accumulation, and spring green‐up dates all changed through time, with different herds experiencing different rates and directions of change. We conclude that elk migration is plastic, is a direct response to environmental cues, and that these environmental cues are not changing in a consistent manner across the GYE. The impacts of changing elk migration timing on predator–prey dynamics, carnivore–livestock conflict, disease ecology, and harvest management across the GYE are likely to be significant and complex. Abstract : Seasonal elk migrations occur in multiple herds across the Greater Yellowstone Ecosystem. These migrations are affected by snow melt and forage conditions, both of which are affected by climate. Here, we examine how changes in the snow and forage are affecting elk migration timing across this iconic ecosystem.